Penerapan Sustainable Livelihood Asssessment (SLA) dalam Menyusun Rencana Aksi Perhutanan Sosial: Studi Kasus di Desa Sidorejo, Kenduruan, Tuban - Maimunah; Kristiawan; Mustikaningrum, Dhina; Eka Lestari, Sulistyani; Prasetyo S, Hery (Jurnal Hutan dan Masyarakat, 2023)
The forest management system in Tuban Regency refers to government forestry regulations which aim to achieve equity and development based on social justice for all Indonesian people. One of the programs in the forestry sector that supports this goal is the Social Forestry program. This research took place in Sidorejo Village, Kenduruan, Tuban Regency. To develop social forestry action plan, this research used Sustainable Livelihood Assessment (approach) as a tool. During SLA process, LMDH members analyze forest areas, institutions, owned capital, problems and action plans. SLA topics related to community life can be an entry point for LMDH Wonorejo, Sidorejo Village, Tuban Regency to understand the problems of implementing forestry partnerships in their area. The results of the SLA show that issues related to members' human and financial resources are two basic things that must be accommodated in the preparation of a social forestry action plan. Therefore, LMDH proposed the Nganget Warm Water Baths tourism development program as a priority for the social forestry action plan.